Maintaining collective memory existence through Gelumpai Manuscripts preservation at the South Sumatra Museum - Saputra, Dandi; Rusmana, Agus; Rizal, Edwin (Jurnal Kajian Informasi dan Perpustakaan, 2023)
This research is based on the case of the well-preserved collection of Gelumpai Manuscripts, which is estimated to be centuries old and believed to date back to the year 1300 C. The manuscripts serve as authentic evidence of Islamic civilization in Palembang at that time and can strengthen historical value through the collective memory of the nation. The study aimed to determine the manuscript’s supporting factors and the Gelumpai Manuscript preservation process. The research method used was qualitative with a case study approach. The research object was the Gelumpai Manuscript, which used the Ka Ga Nga script. Data was obtained through interviews, field observations, and related documentation studies. The results showed that several supporting factors for the preservation of this manuscript included adequate humidity, ideal light intensity, and effective protection against pests and pollution. This means that the South Sumatra Museum has implemented the appropriate standard. The museum carried out preservation by coating the manuscripts with white oil and periodically cleaning and checking the collection in the storage room. Furthermore, this museum held conservation support activities such as Museum Goes to School, Museum Goes to Village, and Collaboration Exhibitions, which were held to educate the public about the specialty of the Gelumpai Manuscript. So, the society will work together to maintain the existence of the collective memory contained in the manuscript.